4D label-free proteomics analysis of oxygen-induced retinopathy with or without anti-VEGF treatment - Xu, Zhaokai; Wu, Yubo; Mao, Jianbo; Chen, Yiqi; Chen, Huan; Zhang, Shian; Yu, Jiafeng; Deng, Xinyi; Shen, Lijun (BMC genomics, 2024)
Oxygen-induced retinopathy (OIR) animal model is widely used for retinopathy of prematurity (ROP) researches. The purpose of this study was to identify proteins and related pathways of OIR with or without anti-vascular endothelial growth factor (VEGF) treatment, for use as biomarkers in diagnosing and treating ROP. Nine samples were subjected to proteomic analysis. Retina specimens were collected from 3 OIR mice, 3 OIR mice with anti-VEGF treatment and 3 normal mice (control group). Liquid chromatography-tandem mass spectrometry analysis was performed using the 4D label-free technique. Statistically significant differentially expressed proteins, gene ontology (GO) terms, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway representations, InterPro (IPR) and protein interactions were analyzed. In total, 4585 unique proteins were identified as differentially expressed proteins (DEPs). Enrichment analysis of the GO and KEGG indicated functional clusters related to peptide biosynthetic and metabolic process, cellular macromolecule biosynthetic process and nucleic acid binding in OIR group. For anti-VEGF treatment group, DEPs were clustered in DNA replication, PI3K/Akt signaling pathway and Jak/STAT signaling pathway. Proteomic profiling is useful for the exploration of molecular mechanisms of OIR and mechanisms of anti-VEGF treatment. These findings may be useful for identification of novel biomarkers for ROP pathogenesis and treatment.